2015
DOI: 10.2217/fmb.14.94
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing: A Therapeutic Approach to Combat Influenza Virus Infections

Abstract: Selective gene silencing technologies such as RNA interference (RNAi) and nucleic acid enzymes have shown therapeutic potential for treating viral infections. Influenza virus is one of the major public health concerns around the world and its management is challenging due to a rapid increase in antiviral resistance. Influenza vaccine also has its limitations due to the emergence of new strains that may escape the immunity developed by the previous year's vaccine. Antiviral drugs are the primary mode of prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…RNA inhibitors are able to regulate the expression of influenza viral RNAs. Accordingly, viral genes became a potential target and RNA inhibitors may be effective in influenza treatment (300).…”
Section: Other Targets and Strategiesmentioning
confidence: 99%
“…RNA inhibitors are able to regulate the expression of influenza viral RNAs. Accordingly, viral genes became a potential target and RNA inhibitors may be effective in influenza treatment (300).…”
Section: Other Targets and Strategiesmentioning
confidence: 99%
“…In this application, several siRNAs targeting conserved regions of the influenza virus genome have been combined to form a cocktail that has a multitargeted approach. 88 Furthermore, Rajput et al reported that when NS1-specific siRNA was administered in experimental mice, a 92% reduction was observed in the levels of NS1 gene expression in the lungs. 98 Significant decrease in cytokine levels and virus titers in the lungs were also observed.…”
Section: Possibility Of Use As Anti-influenza Agent In Human and Animalsmentioning
confidence: 99%
“…Despite progress made in the 20 th century with the introduction of antibiotics, vaccines and antivirals, there are no specific interventions for most respiratory infections of viral origin. Although, the recent years have witnessed a tremendous development in the management of respiratory viruses including influenza and other respiratory viral infections, the world still suffers from these viral infections every year leading to an increase in morbidity and mortality [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%